First report on economic and social cohesion 1996. (Office for Official Publications of the European Communities, 1996)
As provided under Article 130B of the Treaty on European Union, the Commission presents its first cohesion report on the progress made towards achieving economic and social cohesion and on the manner in which the various means provided for in this article have cotributed to it. The report aims to answer four major questions: have economic and social disparities between Member States, regions and social groups narrowed over time? what had been the role and the achievements of Member States' policies in this respect? how have the Union's non-structural policies responded to the Treaty obligation to take account of cohesion objectives? what has been the effect of the Union's structural policies? In so doing, the report attempts to draw out the implications for policy at both the Member State and Union levels.